An engineering design and financial implications of a proposed sanitary landfill in the University of the Philippines Los Baños. - Sundo, M. B.; Rola, W. R.; Dorado, M. A.; Madlangbayan, M. S. (2003)
The study provided an engineering design and financial implications of a proposed new sanitary landfill in the University of the Philippines Los Baños, Laguna, Philippines. Landfill site suitability analysis was guided by the implementing rules and regulation (IRR) of Republic Act (RA) 9003 or Ecological Solid Waste Management Act of 2000. The engineering design of the new UPLB sanitary landfill system strictly follows the design guidelines of the 1984 Sanitary Landfill Engineer Manual of the US Army Corps of Engineers. The liner system was designed based on the typical clay subsoil preparation for a standard sanitary landfill. The proposed landfill liner system employed is composed of a compacted low permeability soil and a geo-membrane. The design also incorporated the minimization of leachate generation by providing low permeability soils cover with low swell and shrink tendency upon wetting and drying to avoid cracking, thus, prevents proliferation of disease-causing vector from exposed waste. The final cover consisting of several layers with different characteristics was also proposed. Ideal location of at least two observation wells was also recommended for groundwater quality monitoring. Return on investment on the proposed sanitary landfill was assessed in terms of the project's financial internal rate of return (FIRR), benefit cost ratio (BCR) and net present value (NPV). The FIRR (20%), NPV (Php11.72 million), and BCR (1.6) figures imply that the project is financially sound. Likewise, sensitivity tests indicate that the landfill project is most vulnerable to output price decreases from tipping fees and other sources of revenues than an increase in the cost of production from operations and maintenance.
Keywords: Sanitary landfills; University of the Philippines (Los Baños)